Efficacy of Activated Charcoal Prepared from Livistona chinensis Seeds for Water Purification - Hatuwal, Sristi; Aryal, Geeta; Giri, Jyoti (Journal of Nepal Chemical Society, 2025)
This study explores the efficacy of activated charcoal derived from Livistona chinensis (Chinese fan palm) seeds for water purification. Activated charcoal was produced through chemical carbonization using concentrated sulphuric acid and neutralized with sodium bicarbonate solution. Fourier Transform Infrared Spectroscopy (FTIR) revealed significant structural changes in the charcoal, indicating enhanced adsorption sites. The practical efficacy of the activated charcoal was evaluated by treating it with two water samples, underground water (S1, Patan, Lalitpur) and surface water (S2, Ranipokhari, Kathmandu). Comprehensive water quality analysis (pH, conductivity, total dissolved solid (TDS), total hardness (TH), chloride, dissolved oxygen, heavy metals (Fe, Mn, Ni, Zn, Cd, Pb) was performed before and after treatment using standard methods and compared against WHO/NDWQS standards, and assessing changes in these parameters. Results demonstrated that the activated charcoal significantly reduced electrical conductivity and TDS, eliminated TH, and lowered chloride levels by 70–75% in both samples. It also effectively reduces concentrations of heavy metals such as iron, manganese, nickel, and cadmium as determined by Atomic Absorption Spectrophotometer (AAS). These findings underscore the potential of Livistona chinensis seeds as a cost-effective and sustainable raw material for the production of high-capacity activated charcoal, providing a viable strategy for enhancing water quality, especially in rural and resource-limited areas.